2019
DOI: 10.4314/ijbcs.v12i5.12
|View full text |Cite
|
Sign up to set email alerts
|

Anticoccidial activity of <i>Carica papaya</i> and <i>Vernonia amygdalina</i> extract

Abstract: The anticoccidial effect of C. papaya and V. amygdalina crude juice was tested on 100 Eimeria tenella experimentally infected day-old Isa-brown male chicks in a completely randomized design, as an alternative coccidiosis control measure. Each chick received 3 x 10 4 E. tenella oocysts doses. The first and the second groups were orally treated with papaya and vernonia juice, for consecutive 5 days. The third and the fourth groups were medicated (sulfadimidine) and unmedicated controls. The papaya treatment impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 24 publications
3
19
0
1
Order By: Relevance
“…The findings are consistent with the results of Christaki et al (2004) who obtained a reduction in lesion scores, bloody diarrhea and oocysts per gram in feces (OPG) with Agrimonia eupatoria, Echinacea angustifolia, Ribes nigrum and Cinchonas uccirubra extract treatment against chicken coccidiosis. Also, Dakpogan et al (2018), reported a reduction in oocyst excretion rate of 56% in Eimeria tenella experimentally infected chicks, treated with Carica papaya extract. Other authors have reported the anticoccidial activity of several medicinal plants (Youn and Noh 2001, Sujikara 2000, Arczewska and Swiatkiewicz 2010, Emilio et al, 2013, Loredana et al 2015.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The findings are consistent with the results of Christaki et al (2004) who obtained a reduction in lesion scores, bloody diarrhea and oocysts per gram in feces (OPG) with Agrimonia eupatoria, Echinacea angustifolia, Ribes nigrum and Cinchonas uccirubra extract treatment against chicken coccidiosis. Also, Dakpogan et al (2018), reported a reduction in oocyst excretion rate of 56% in Eimeria tenella experimentally infected chicks, treated with Carica papaya extract. Other authors have reported the anticoccidial activity of several medicinal plants (Youn and Noh 2001, Sujikara 2000, Arczewska and Swiatkiewicz 2010, Emilio et al, 2013, Loredana et al 2015.…”
Section: Discussionmentioning
confidence: 96%
“…Coccidiosis is a parasitic disease that affects animals such as poultry, mammals, rodents and lagomorphs, etc. and caused by a protozoan of the phylum Apicomplex, family Eimeridae and genus Eimeria (Dakpogan et al, 2018). It is a digestive parasitosis due to the presence and replication of coccidian sporozoïtes in the digestive epithelium of birds and is characterized by a massive destruction of epithelial cells with clinical signs such as severe haemorrhagic diarrhea that can lead to death with 50 % or even 90% mortality rate especially in young chickens (Vermeulen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need arises, therefore, to examine less expensive and appropriate technology in addressing the problem of uncontrolled breeding in tilapia using suitable natural alternatives that are biodegradable and biological inhibitory agents. Many plants such as Carica Papaya have successfully been used to induce sterility in laboratory animals (Abbas and Abass, 2011) and as medicinal plants in rural communities to cure many human and animal diseases (Dakpogan et al, 2018). Carica papaya (Linn) is one of the economically important fruit trees in the Caricaceae family (Nwiloh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Carington et al (2007) in South Africa and Dakpogan et al (2013) in Benin have estimated the financial cost of anticoccidial drugs used per laying hen during its life cycle at US $ 0.30. The intensive use of anticoccidial drug is increasingly worrisome because of anticoccidial drug-resistant coccidia strain emergence (Dakpogan et al, 2018) and the presence of drug residues in poultry products prejudicial to consumer health (Cannavan et al, 2000 ;Mortier et al, 2005 ;Danaher et al, 2008). Conventional vaccines were developed to control coccidiosis (Williams 2002;Chapman et al, 2002;Li et al, 2005).…”
Section: Introductionmentioning
confidence: 99%